Era Kemudahan Akses Internet sebagai Pendorong Tindakan Kekerasan Seksual oleh Anak : Studi Kasus di Kapanewon Tanjungsari, Kabupaten Gunungkidul - Sauzan Vidya Rastratama Mitra (Mahkamah : Jurnal Riset Ilmu Hukum, 2024)
In today's era of globalization, cases of sexual violence against children are becoming more and more concerning, making parents have to be more vigilant in protecting their children. Children who often watch various pornographic or immoral shows will be easily motivated to practice what they see on their cellphone screens through the internet media, allowing violations of the norms that live in society and religious teachings, including sexual violence, the majority of whose victims are still children. This can be seen from the lack of filtering of the types of media that can be watched by children. Communication is one solution in preventing sexual violence against children. In addition to communication being established so that a family can be open and harmonious, in this case communication is very important for the role of parents to be able to provide protection to children through communication between the two so that parents can equip and protect children from crimes that lurk children. So parents need to communicate and monitor the actions taken by children in their daily lives, especially things that are attached to the child, especially cellphones, which are currently very close to children in the process of playing. So in this study, an in-depth analysis was carried out on the factors that caused acts of sexual violence committed by children in learning about one of the cases in Kapanewon Tanjungsari, Gunungkidul Regency.